Avaliação da estabilidade oxidativa do biodiesel obtido do óleo de amendoim (Harachis hypogaea) durante armazenamento - Pinto, Luzenir Monteiro (2013)
Biodiesel, mixture of alkyl esters of long chain fatty acids, is oxidized during storage, due to the degradation of the unsaturated esters when in contact with oxygen from atmosphere or due to changes of temperature and humidity. In peanut biodiesel, oleic and linoleic esters represent more than 80 % of the total ester amount determining the biodiesel quality. In this work, ethylic and methylic biodiesels were stored for 12 months of storage in oven at 43°C and their oxidative stability were evaluated by physic-chemical analysis, established by the ANP standard: acidity index, kinematic viscosity at 40°C, specific mass, oxidation stability at 110°C. During the five months of storage, values of acidity index, viscosity, specific mass and humidity were in agreement to the limits established by the standard. After that, biodiesels presented different behaviors. The methylic biodiesel had higher values of acidity index, viscosity, humidity than ethylic one, indicating that a higher degradation occurred. Preliminary essays related to the oxidative stability of peanut biodiesel containing the antioxidants: alfa-tocoferol, terc-butil hidroquinona (TBHQ) and green tea ethanolic extract (GTEE) were done, using Rancimat and PDSC. The antioxidant addition improved the oxidative stability of peanut biodiesel. The efficiency order of the antioxidants was TBHQ > EECV > -tocoferol.